Homework in the Foundation Phase: Perceptions of principals of eight public primary schools in Johannesburg - Misheck Ndebele (South African Journal of Education, 2018)
This article reports on a qualitative study done in Johannesburg, South Africa, which investigated attitudes of primary school principals of eight public primary schools towards the use of homework in teaching and learning in the Foundation Phase (which comprises the first three grade levels of primary schooling). Using a semi-structured interview, the study focused on the principals’ perceptions of homework in general, whether homework policies existed in their schools, and the extent to which parents were involved in their children’s homework. To obtain a representative set of findings, purposive sampling was used to recruit two participating principals from schools in each of the following geographical and socio-economic settings: inner city, peri-urban, suburban and township. The findings indicated that although the purpose and value of homework remains debatable, the participating principals viewed homework as a valuable tool in teaching and learning. The principals expressed the belief that parents from low-income environments regarded homework as important, as did their higher-income counterparts, but poorer parents were less involved in their children’s homework. The study concludes with recommendations for education policy-makers, as well as primary school administrators and parents, regarding the use of homework in primary schools.